An ultra-high-vacuum rotating sample manipulator with cryogenic cooling - Tee, Xian Yang (2021)
We report a homebuilt ultra-high-vacuum (UHV) rotating sample manipulator with cryogenic cooling. The sample holder is thermally anchored to a built-in cryogenic cold head through flexible copper beryllium strips, permitting continuous sample rotation. A similar contact mechanism is implemented for electrical wiring to the sample holder for thermometry. The apparatus thus enables continuous sample rotation at regulated cryogenic temperatures in a UHV environment. We discuss applications of this apparatus for cryogenic sputtering.